Effects of Coercion on Contract in Islamic (Hanafi Jurisprudence) and Civil Code of Afghanistan - Amin, Sharifullah; Khairkhwah, Khair Mohammad; Stanikzai, Abdul Naser (Integrated Journal for Research in Arts and Humanities, 2022)
In this research paper, the main question is what are the Effects of coercion on contract in Islamic (Hanafi jurisprudence) and civil code of Afghanistan? the purpose of this study is to examine the nature of coercion in Islamic Sharia (Hanafi Jurisprudence) and Afghan Civil Code and to compare its impact on contract. using descriptive-qualitative methods as well as library resources (documents, books, as well as credible internet sites and articles) it has been proven that these legal systems are the same or have different positions on this issue; as a result, it has been found that the main factors of both legal systems similarities are in the adoption of the Civil Code, mostly the Majalat alahkam aleadlia and the Egyptian Civil Code have been used directly.